Valproic Acid-Induced Myoclonus in a Demented Patient: A Case Report - Tina M. Gardner; Rehan Aziz; Sunanda Muralee; Rajesh R. Tampi (Case Reports in Medicine)
Valproic acid and its derivatives are now commonly used to treat various psychiatric disorders in the elderly. Data indicates that the elderly patients are more susceptible to developing neuropsychiatric complications when treated with these medications. In this report, we describe the case of a 66-year-old woman with early-onset, Alzheimer's type dementia, who developed myoclonus when treated with a valproic acid preparation for behavioral disturbances associated with the dementia.